Investigation of microRNA-protein complex recruitment to the hepatitis C virus untranslated regions - Conrad, Karl Dominik; Justus Liebig University Giessen (My University, 2013)
Hepatitis C virus belongs to the family of Flaviviridae and contains a single stranded RNA genome in positive orientation. The genome carries a single polyprotein open reading frame (ORF), which is flanked by two highly structured RNA stretches, the 5 - and 3 -untranslated regions (UTRs). In these UTRs several secondary structures were identified to be necessary for HCV translation and replication.The internal ribosome entry site (IRES), which is required for translation, comprises three of the four stem loops present in the 5 -UTR. In addition two microRNA-122 (miR-122) binding sites are located upstream of the IRES. The 3 -UTR comprises a variable region (VR), a poly U/C tract and three conserved stem loops. In the VR an additional miR-122 binding site was identified. miR-122 was shown to stimulate HCV translation and replication possibly by protecting the HCV RNA from degradation.This work focused on the question whether miR-122 recruits a microRNA-protein complex to its binding sites on the HCV RNA and which components this complex contains. Towards this end an anti-Argonaute (Ago) protein-specific HCV RNA co-immunoprecipitation was developed. Using this method it could be shown that two of the four members of the Ago protein family, Ago1 and Ago2, are recruited to the HCV RNA in a miR-122 dependent manner. For the miR-122 binding site in the VR of the 3 -UTR it has also been shown that Ago2 can be recruited by miR-122. This however is only the case when four nucleotides located in a stem loop in the NS5B coding region are present. These findings give rise to the assumption that for this miR-122 binding site not only the seed sequence but also four additional nucleotides located close to the 3 -end of the miR-122 bind to the HCV RNA.Finally, employing a time course assay it has been shown that miR-122 prolongs the half-life of a wild type HCV reporter RNA compared to a mutant that is not able to bind miR-122 or compared to the wild type in presence of a control miR-122. This experiment also shows that, besides stabilizing the HCV RNA, miR-122 seems to directly stimulate HCV translation.Thus, it seems that miR-122 recruits a microRNA-protein complex and positively influences the HCV life cycle via two different mechanisms. Firstly, miR-122 enhances HCV RNA stability, most likely by protecting it from degradation. Secondly, miR-122 improves HCV translation efficiency probably by changing the IRES structure to a conformation favorable for translation.

Das Hepatitis C Virus (HCV) gehört zu der Familie der Flaviviridae und besitzt ein einzelsträngiges RNA-Genom in (+)-Strang-Orientierung. Dieses Genom enthält einen einzelnen offen Leserahmen für das Polyprotein. Dieser ist von 5 - und 3 -nicht translatierten Regionen (UTRs) flankiert, in welchen sich viele Sekundärstrukturen befinden, die unerlässlich für die Translation und Replikation des Virus sind.Die sogenannte internal ribosome entry site (IRES) in der 5 -UTR besteht aus drei Haarnadelstrukturen und ist unerlässlich für die Translationsinitiation des HCV ist. Zusätzlich besitzt die 5 -UTR zwei microRNA-122 (miR-122) Bindestellen stromaufwärts der IRES. Die 3 -UTR umfasst eine variable Region (VR), einen poly-U/C-Trakt sowie drei konservierte stem loops. Auch hier befindet sich, im Bereich der VR, eine miR-122 Bindungsstelle. Des Weiteren wurde für miR-122 nachgewiesen, dass sie stimulierend auf die Translation und Replikation wirkt, möglicherweise indem sie die HCV-RNA vor Abbau schützt.Das Hauptaugenmerk der vorliegenden Arbeit lag auf der Frage, ob miR-122 einen microRNA-Proteinkomplex (miRNP) an die HCV-RNA rekrutiert und welches die Proteinkomponenten dieses Komplexes sind. Zur Untersuchung dieser Fragestellung wurde eine Argonaute (Ago) Protein spezifische HCV-RNA Koimmunpräzipitation entwickelt. Mit dieser Methode konnte nachgewiesen werden, dass zwei der vier Mitglieder der Ago-Proteinfamilie, Ago1 und Ago2, durch miR-122 an die HCV-RNA rekrutiert werden. Bezüglich der miR-122 Bindestelle in der VR der 3 -UTR konnte gezeigt werden, dass abhängig von miR-122 Ago2 auch hier binden kann allerdings nur, wenn neben der bekannten miR-122 Bindesequenz auch vier Nukleotide der NS5B-kodierenden Region vorhanden sind. Folglich ist, nicht nur die seed-Sequenz der miR-122 notwendig für die effiziente Bindung an die HCV 3 -UTR, sondern auch vier Nukleotide am 3 -Terminus von miR-122.Zusätzlich wurde ein Zeitverlaufsversuch durchgeführt, um die Stabilität der HCV-RNA zu testen. Dabei wies ein HCV-Reporter-RNA eine höhere Halbwertszeit in Anwesenheit von miR-122 auf als ein vergleichbare Mutante, die miR-122 nicht binden kann, oder der Wildtyp in Anwesenheit einer Kontroll-miR. Zusätzlich scheint miR-122 neben der Stabilisierung der HCV-RNA auch einen direkten positiven Effekt auf die HCV Translation zu haben.Zusammengefasst rekrutiert miR-122 einen miRNP-Komplex an die HCV-RNA und beeinflusst den Lebenszyklus des HCV positiv durch zwei unterschiedliche Mechanismen. Zum einen erhöht miR-122 die Stabilität der HCV-RNA, möglicherweise durch die Verhinderung des Abbaus der HCV-RNA. Zum anderen verstärkt miR-122 die HCV-Translationseffizienz, möglicherweise dadurch, dass die Bindung von miR-122 die Struktur der IRES beeinflusst und diese in eine Konformation bringt die vorteilhaft für die Translation ist.
Untersuchung zur Rekrutierung von mikroRNA-Komplexen an die untranslatierten Regionen des Hepatitis C Virus Genoms
Keywords: mikro-RNA; Hepatitis C Virus; Translationsregulation; Hepatitis C virus; microRNA; translation regulation; ddc:570